2022
DOI: 10.1136/bmj-2021-068177
|View full text |Cite
|
Sign up to set email alerts
|

Early phase clinical trials extension to guidelines for the content of statistical analysis plans

Abstract: This paper reports guidelines for the content of statistical analysis plans for early phase clinical trials, ensuring specification of the minimum reporting analysis requirements, by detailing extensions (11 new items) and modifications (25 items) to existing guidance after a review by various stakeholders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 31 publications
0
31
0
Order By: Relevance
“…15 More recent guidelines for the contents of statistical analysis plans in early phase trials include specification of estimands. 39 However, this review found that some trials defined their estimands in their protocol, which differs from a recent review of protocols published in October 2020 in Trials and BMJ Open, where no protocols explicitly defined the estimand, and estimands could be inferred in only 26% of protocols. 17 Use of estimands in this review might have been higher as we considered the six leading general medical journals and non-published protocols submitted as supplementary material.…”
Section: Research In Contextmentioning
confidence: 61%
See 2 more Smart Citations
“…15 More recent guidelines for the contents of statistical analysis plans in early phase trials include specification of estimands. 39 However, this review found that some trials defined their estimands in their protocol, which differs from a recent review of protocols published in October 2020 in Trials and BMJ Open, where no protocols explicitly defined the estimand, and estimands could be inferred in only 26% of protocols. 17 Use of estimands in this review might have been higher as we considered the six leading general medical journals and non-published protocols submitted as supplementary material.…”
Section: Research In Contextmentioning
confidence: 61%
“… 15 More recent guidelines for the contents of statistical analysis plans in early phase trials include specification of estimands. 39 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As with every large-scale trial, smaller scale feasibility and pilot trials should be conducted to inform final study features including recruitment and retention procedures, fidelity of intervention delivery, selection of primary and secondary outcomes and protocols for outcomes assessment, infrastructure for data management and ethical oversight across multiple sites. Consolidated Standards of Reporting Trials (CONSORT) and other guidelines for the design and reporting of pilot clinical trials are now widely available [221,222].…”
Section: Randomized Controlled Trialsmentioning
confidence: 99%
“…It is beyond the scope of this paper to discuss situations where subjects experience either near DLTs or devastating DLTs and clinician's judgments on risk‐benefit are factored into the decision. While inclusion of this type of flexibility in the protocol is permissible, a recent survey by Homer and colleagues 14 shows that dose escalation decisions, stopping criteria, and interim go‐no‐go criteria are often poorly documented, resulting in ambiguous decisions to escalate. Critical assessment of dose escalation is only possible if the design, conduct, and analysis are predefined thoroughly and clearly documented.…”
Section: Practical Considerationsmentioning
confidence: 99%